Enhancement of exciton binding energies in ZnO/ZnMgO multi-quantum wells - Makino, T. (2009)
The effect of confinement on the exciton binding energies has been systematically investigated for two series of ZnO/ZnMgO multiquantum wells with various well widths and barrier heights. The exciton binding energies were extracted from the energy difference between the stimulated emission band induced by inelastic exciton–exciton scattering and the free exciton absorption band. The binding energies of excitons are found to be sensitively dependent on the well widths. The experimental results of the well width dependence of binding energies are in good agreement with Coli and Bajaj’s theoretical calculations for these structures [G. Coli and K. K. Bajaj, Appl. Phys. Lett. 78, 2861 (2001)]. The remarkable reduction in coupling strength between excitons and longitudinal optical phonons is closely correlated with the enhancement of the exciton binding energy, indicating that the stability of excitons is greatly increased by the enhancement of exciton binding energy in quantum wells.